Gênero, finanças públicas e direitos humanos: o inventário das ausências - Rezende, Mirela Faleiros (2019)
The Brazilian social context is marked by a state and social structure that leads to imbalances and discrimination that prevent the full achievement of women's human rights. Taxation is part of this state structure marked by those asymmetries. Thus, from these premises the present work seeks to investigate the social impacts of taxation for women. To this end, it draws on the bases of fiscal sociology that develops an interdisciplinary analysis of public finances. This science allows us to identify the gender-tax relationship as well as its consequences. International studies has shown that taxation has a gender bias and, based on these studies, we seek to investigate if the Brazilian tax system shows a gender bias.